Addition to the knowledge on the moth fauna (Insecta: Lepidoptera) of Bosnia and Herzegovina and Croatia - Toni Koren; Dejan Kulijer (Natura Sloveniae)
Additions to the moth fauna of Bosnia and Herzegovina and Croatia are given. We report on first observations of five species and on reconfirmation of one species after eight decades. In Croatia, we recorded the species Eublemma cochylioides (Guenée, 1852) for the first time, while Eublemma himmighoffeni (Millière, 1867) has been confirmed in the country after 85 years. We report on the first observation of five moth species for Bosnia and Herzegovina: Triodia adriaticus (Osthelder, 1931), Eumera regina Staudinger, 1892, Dryobotodes monochroma (Esper, 1790), Lithophane lapidea (Hübner, [1808]) and Nycteola columbana (Turner, 1925). Even though these records could be expected due to species general distributions, they fill the knowledge of moth diversity of both countries and the wider region.